Cardiomyocyte differentiation: Experience and observations from 2 laboratories - Patten, Victoria; Chabaesele, I; Sishi, Balindiwe; Van Vuuren, Derick (SA Heart Journal, 2017)
The undifferentiated clonal cell line, H9c2, derived from left ventricular rat heart tissue, has been extensively used in cardiovascular research. In the present study, 2 independent laboratories aimed to investigate the cells’ capacity to differentiate into distinct cardiac-like cells. Undifferentiated H9c2 cells were supplemented daily for a period of 6 - 12 days, with varying concentrations of retinoic acid (RA) (10nM, 30nM and 1μM), in standard cell culture medium containing either 1% foetal bovine, or horse serum, in order to stimulate differentiation of the cells into a more cardiac-specific phenotype. Light microscopy confirmed some degree of morphological change associated with differentiation, and a significant increase in oxidative phosphorylation following RA treatment was observed. However, Western blot probing for the cardiac-specific markers Cardiac Troponin T (cTnT) and Myosin Light Chain-2v (MLC2v) indicated little to no differentiation, although immunocytochemistry indicated the presence of cTnT expression. Thus, it was found that the differentiation protocol induced differentiation in some, but not all cells, thereby generating a heterogeneous cell population. Our findings suggest that the H9c2 cell line may display some degree of resistance to differentiation. This should be kept in mind when considering to use this model for cardiovascular research.